Morphology of the tongue of the Marsh deer (Blastocerus dichotomus) - Machado, Marcia R. F. (2016)
The aim was to describe the morphology of the tongue of the Marsh deer (Blastocerus dichotomus), the largest deer of the Brazilian fauna, since there is little detailed information on their morphology. Tongues of eight adult Marsh deers, belonging to Projeto cervo-do-pantanal de Porto Primavera were analyzed for their macroscopic aspects and by light microscopy. The Marsh deer tongue occupies most of the oral cavity, where the root and body are fixed caudally by the hyoid bone, and in its middle portion by the frenulum linguae; its free apex is flat and plane, has little prominent torus lingae and there is no demarcation of fossa linguae. The lateral and ventral surfaces are covered by a thin mucosa; however the dorsal surface is covered by thick mucosa, although soft. On the dorsal surface are the papillae: filiform, conical, lenticular, fungiform and vallate. Histologically was found that the mucosa has a stratified squamous epithelium, the lamina propria consists of connective tissue rich in collagen fibers arranged in several directions, where there is abundant vascularization and accumulation of lymphoid tissue.